KINETICS OF GASEOUS TOLUENE ADSORPTION ON CANDLENUT SHELL ACTIVATED CARBON - Audy D Wuntu; Vanda S Kamu (JURNAL ILMIAH SAINS, 2013)
KINETICS OF GASEOUS TOLUENE ADSORPTION ON CANDLENUT SHELL ACTIVATED CARBON ABSTRACT Adsorption kinetics of gaseous toluene on activated carbon prepared from candlenut shell had been studied. The research was performed by examining adsorption data, which was obtained in previous research, over several rate equations, which were: (1) Lagergren’s pseudo first order rate equation, (2) Ho’s pseudo second order rate equation, (3) Elovich’s equation, and (4) persamaan Ritchie’s equation. The result showed that the data of toluene adsorption on candlenut shell activated carbon fits the Ho’s pseudo second order rate equation and, hence, the model is the most applicable model for the adsorption. Calculation from linear regression of Ho’s pseudo second order rate equation gave the equilibrium adsorption capacity value of 56,069 mg g-1, second order rate constant of 3,54x10–4 g mg-1 min-1, and initial adsorption rate of 1,112 mg g-1 min-1. Keywords: adsorption, candlenut, activated carbon, toluene KINETIKA ADSORPSI GAS TOLUENA PADA KARON AKTIF TEMPURUNG KEMIRI ABSTRAK Studi mengenai aspek kinetika adsorpsi toluena pada arang aktif yang terbuat dari tempurung kemiri telah dilakukan. Penelitian dilakukan dengan menguji data adsorpsi yang telah diperoleh pada penelitian terdahulu menggunakan empat persamaan laju adsorpsi, yaitu (1) persamaan laju pseudo order pertama Lagergren, (2) persamaan laju pseudo order kedua Ho, (3) persamaan Elovich, dan (4) persamaan Ritchie. Hasil kajian menunjukkan bahwa model kinetika dengan persamaan laju pseudo order kedua Ho adalah yang paling sesuai diaplikasikan untuk adsorpsi gas toluena pada arang aktif tempurung kemiri. Dari persamaan linear untuk model kinetika pseudo order kedua Ho diperoleh nilai kapasitas adsorpsi pada kesetimbangan sebesar 56,069 mg g-1, konstanta adsorpsi sebesar 3,54x10–4 g mg-1 menit-1, dan laju adsorpsi awal sebesar 1,112 mg g-1 menit-1. Kata kunci: adsorpsi, kemiri, karbon aktif, toluena